The Future of the IMF - Caballero, Ricardo J (American Economic Review, 2003)
In spite of significant institutional and macroeconomic reforms over the last decade or two, capital flows to developing economies remain highly volatile. In 1996, net private capital flows to emerging markets reached US$230 billion; by 1997 these flows had been cut in half; by 1998 halved again; and after a mild recovery during 1999, flows fell in 2000 and 2001 to slightly over one-tenth the level of 1996. With the exception of developing Asia, 2002 does not look much rosier (see International Monetary Fund, 2002 p. 12 [table 1.3]). The economic, political, and social costs of these large swings in capital flows are enormous. The most vivid examples are seen in the economies that experience deep crises, including (since 1997) Thailand, Indonesia, Malaysia, Korea, Russia, Brazil, Turkey, and Argentina. While in many instances there are important domestic deficiencies behind these reversals, there is also a well-founded sense that international financial markets often exacerbate the problem. It is not surprising, then, that as with the debt crisis of the early 1980’s and the Mexican crisis of the 1990’s this new wave of crises has led to innumerable calls for deep reform to these markets. Nowhere is this more apparent than in the design of new “rules of engagement” for the International Monetary Fund. The important work of multiple official and unofficial commissions, leveraged by its own rethinking, promises to transform this institution from the ground up. In a nutshell, most experts agree that the International Monetary Fund should be much more focused, transparent, predictable, and quick in its interventions, and its role limited to surveillance (pre-crisis) and lenderof-last-resort/bankruptcy-court (during crises) activities. This seems right. I believe, however, that by focusing almost exclusively on the needs of countries undergoing deep crises (highly illiquid and “bankrupt” economies) these reform proposals have left unaddressed a significant fraction of the costs associated with capital-flows reversals. An important share of these costs are borne by countries that experience deep contractions but do not undergo full-blown crises, and much of the cost experienced by those countries that do fall into deep crises is experienced well before the open crisis phase develops. Often, the latter is just the final stage of a prolonged and politically thorny economic period of sharply reduced access to international capital markets. Surely, the anticipation of more orderly resolution and access to a few credit lines, should the open crisis phase arrive, would (by backward induction) eliminate some of the costs that precede these events as well. But this benefit is indirect only and relies on a chain of reasoning that requires more rationality and trust in the new system † Discussants: Stanley Fischer, Citigroup; Allan Meltzer, Carnegie Mellon University; Jeffrey Sachs, Columbia University; Nicholas Stern, World Bank.